Bienestar subjetivo en adolescentes con actividades extracurriculares de alta exigencia - Espinosa Requesens, Marlon Frank (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The aim of this study was to establish a comparison between the level of Subjective Well being present in a group of adolescents and young people linked to extracurricular activities of high demand and a second group that were not linked to this type of activities. In order to fulfill this objective, three studies were carried out, in the first one it was designed to design a test that measured Satisfaction with Life (CBSVAJ), it had 244 participants, 177 (72.5%) women and 67 (27.5%) men, with ages between 17 and 24 years (M = 20.82, SD = 3.64). The second study was the design of the Competitive Traits test (CRCA), 348 adolescents participated, 244 (70.1%) were women and 104 (29.9%) men, between 13 and 19 years (M = 16.06, SD = 1.42). The main study showed that adolescents who do high-demand extracurricular activities have higher levels of Subjective Wellbeing. Keywords: Subjective well-being; Satisfaction with life; Competitive traits; Extracurricular activities; Teens and young people.

El objetivo de este estudio fue establecer una comparación entre el nivel de Bienestar Subjetivo presente en un grupo de adolescentes y jóvenes vinculados a actividades extracurriculares de alta exigencia y un segundo grupo que no se vinculaban a este tipo de actividades. Para cumplir con este objetivo se hicieron tres estudios, en el primero tuvo como objetivo diseñar una prueba que midiera la Satisfacción con la Vida (CBSVAJ), contó con 244 participantes, 177(72.5%) mujeres y 67(27.5%) hombres con edades entre 17 y 24 años (M=20.82, DE=3.64). El segundo estudio fue el diseño de la prueba de Rasgos Competitivos (CRCA), participaron 348 adolescentes, 244(70.1 %) fueron mujeres y 104(29.9 %) hombres, de entre 13 y 19 años (M=16.06, DE=1.42). El estudio principal arrojó que los adolescentes que hacen actividades extracurriculares de alta exigencia presentan mayores niveles de Bienestar Subjetivo.
Facultad de Psicología. Maestría en Psicología
Keywords: info:eu-repo/classification/cti/4; FP-M-2020-0141; Satisfacción con la vida; Rasgos competitivos; Adolescentes y jóvenes; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3610